PROFIL TINGKAT KESEGARAN JASMANI SISWA SMA NEGERI 1 TEMBILAHAN HULU - Taqwa Zakariwa; Slamet Slamet; Arev Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Based on observations and direct interviews conducted by researchers at SMA Negeri 1 Tembilahan Hulu, it was found that the physical fitness level of SMA Negeri 1 Tembilahan Hulu students was still very low. The purpose of this study was to determine the level of physical fitness of students of SMA Negeri 1 Tembilahan Hulu. The population of this study were 20 students of class X1 SMA Negeri 1 Tembilahan Hulu. This study uses a total sampling technique where the entire population is used as a sample. Based on the above sample determination, a sample of 20 people was obtained. The data obtained were compared with physical fitness norms. Based on the research results it can be concluded that: The physical fitness of male students is still in the moderate category. This is evidenced by the highest average score of the male students' physical fitness test of SMA Negeri 1 Tembilahan Hulu which is 17.33 = 17. This shows that the physical fitness level of male students of SMA Negeri 1 Tembilahan Hulu is still in the Medium category. This is because the value of 14-17 is classified as moderate. The physical fitness of female students is still in the medium category. This is evidenced by the highest average value of the physical fitness level test for female students of SMA Negeri 1 Tembilahan Hulu, namely 15.6 = 16. This shows that the physical fitness level of female students of SMA Negeri 1 Tembilahan Hulu is still in the Medium category. This is because the grades 14-17 are classified as MediumKey Words: Physical Freshness Level, Students of SMA Negeri 1 Tembilahan Hulu